2006
DOI: 10.1111/j.1095-8312.2006.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple levels of allopatric divergence in the endemic Philippine fruit bat Haplonycteris fischeri (Pteropodidae)

Abstract: As part of a larger comparative phylogeographical study of Philippine fruit bats, I used fragments of the mitochondrial genes cytochrome b and ND2 to investigate phylogeography and diversification in Haplonycteris fischeri , a pteropodid bat endemic to the Philippines but widespread within the archipelago. Genetic diversity in H. fischeri was extremely high in these commonly studied genes, with 101 unique haplotypes in 123 sequenced individuals, although small, continuously isolated islands had less diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 41 publications
(78 reference statements)
2
46
0
Order By: Relevance
“…Analysis of F ST , AMOVA, and Bayesian clustering suggested that there were significant interisland differences; this supports the hypothesis that the open sea formed a significant barrier for bat dispersal, especially when the interisland distance was large, such as between Yonaguni and the other islands. These results are comparable with the data reported for the population of bats on other islands, e.g., populations of Cynopterus nusatenggara (Schmitt et al 1995), Eidolon helvum (Juste et al 2000), and Haplonycteris fischeri (Roberts 2006). In contrast, the disagreement between our results (lack of genetic structure) and the marginal species dispersal on Iriomote Island, as suggested by banding data (Maeda and Matsumoto 2004), might be partly because intercolonial dispersal occurred to an extent that was sufficient to reduce genetic structuring but was insufficient to be detected by the mark-recapture method.…”
Section: Genetic Differentiation and Gene Flowsupporting
confidence: 90%
“…Analysis of F ST , AMOVA, and Bayesian clustering suggested that there were significant interisland differences; this supports the hypothesis that the open sea formed a significant barrier for bat dispersal, especially when the interisland distance was large, such as between Yonaguni and the other islands. These results are comparable with the data reported for the population of bats on other islands, e.g., populations of Cynopterus nusatenggara (Schmitt et al 1995), Eidolon helvum (Juste et al 2000), and Haplonycteris fischeri (Roberts 2006). In contrast, the disagreement between our results (lack of genetic structure) and the marginal species dispersal on Iriomote Island, as suggested by banding data (Maeda and Matsumoto 2004), might be partly because intercolonial dispersal occurred to an extent that was sufficient to reduce genetic structuring but was insufficient to be detected by the mark-recapture method.…”
Section: Genetic Differentiation and Gene Flowsupporting
confidence: 90%
“…In addition to historical events, ecological attributes such as colonization or dispersal abilities should play a role in establishing patterns of genetic differentiation and colonization events (Heaney et al. , 2005; Roberts, 2006; Heaney, 2007). Therefore, both ecological and historical factors may generate intraspecific diversity in island settings, and the integration of the two perspectives is essential in phylogeographical studies.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that substantial gene flow between Panay/Guimaras and Negros ceased at the end of the last Pleistocene ice age when the Panay-Negrosian PAIC broke down into separated islands due to eustatic changes in the sea level. While such a Pleistocene sea level-related model of speciation is rejected in favor of an earlier, Pliocene diversification for, e.g., rodents of the genus Apomys [50] or for the fruit bat Haplonycteris fischeri [51], the latter author suggests that sea-level changes may have played an important role for more recent divergence at the within PAICs level, such as among Negros and Panay. The shortest distance between the two islands today is about 15 km but, due to the presence of Guimaras and several other intervening islets, the longest open water distance is just 5 km.…”
Section: Discussionmentioning
confidence: 99%